Pengaruh Potongan Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan PT SDA Indonesia Surabaya - Putri, Ayu; Mulyati, Diana Juni; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2020)
This study aims to determine the effect of the variable price discounts and service quality on customer satisfaction partially, simultaneously and the variables that dominate. The method used in this research is quantitative research using multiple linear regression analysis methods. The population used in this study is people who make purchases at PT SDA Indonesia Surabaya. The samples used were 100 respondents using accidental sampling techniques. The data collection technique used is the distribution of questionnaires.               This research produces (1) Partially shows the positive influence between the variable price discounts on customer satisfaction PT SDA Indonesia Surabaya (2) The variable service quality also has a positive effect on customer satisfaction PT SDA Indonesia Surabaya (3) Simultaneously also shows the price and service quality together positively to the customer satisfaction of PT SDA Indonesia Surabaya. Keywords: Discounted Prices, Service Quality and Customer Satisfaction